2011
DOI: 10.2337/db11-0689
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Paternally Transmitted Fetal IGF2 Variants and Maternal Circulating Glucose Concentrations in Pregnancy

Abstract: OBJECTIVETo test the hypothesis that polymorphic variation in the paternally transmitted fetal IGF2 gene is associated with maternal glucose concentrations in the third trimester of pregnancy.RESEARCH DESIGN AND METHODSA total of 17 haplotype tag single nucleotide polymorphisms in the IGF2 gene region were genotyped in 1,160 mother/partner/offspring trios from the prospective Cambridge Baby Growth Study (n = 845 trios) and the retrospective Cambridge Wellbeing Study (n = 315 trios) (3,480 samples in total). As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…We found that in a similar model in which phenotypically wild-type pregnant mice carrying litters where around half of the offspring had the H19 gene and the nearby Igf2 control element disrupted, hyperglycaemia and placentomegaly were evident in late pregnancy [67]. We then found similar associations between fetal IGF2 SNPs and maternal glucose concentrations in humans [68], raised glucose concentrations themselves being associated with an increased risk of developing preeclampsia [69].…”
Section: Animal Studiesmentioning
confidence: 51%
See 1 more Smart Citation
“…We found that in a similar model in which phenotypically wild-type pregnant mice carrying litters where around half of the offspring had the H19 gene and the nearby Igf2 control element disrupted, hyperglycaemia and placentomegaly were evident in late pregnancy [67]. We then found similar associations between fetal IGF2 SNPs and maternal glucose concentrations in humans [68], raised glucose concentrations themselves being associated with an increased risk of developing preeclampsia [69].…”
Section: Animal Studiesmentioning
confidence: 51%
“…We suggested that fetal imprinted genes could influence the risk of the mother developing hypertensive disorders in pregnancy and gestational diabetes [5,109]. We have published data consistent with this in terms of raised maternal glucose concentrations in late pregnancy and fetal (paternally expressed) IGF2 in both mice [67] and humans [68]. Preliminary analyses of results from our Cambridge Baby Growth Study cohort suggest that maternal blood pressure will also be associated with polymorphic variation in various fetal imprinted genes.…”
Section: Fetal Imprinted Genesmentioning
confidence: 56%
“…Also, in an animal study by Petry et al (2010), maternal glucose concentrations in pregnant mice were elevated among women carrying pups with targeted disruption of maternally transmitted fetal H19 D13 , which implied that variable fetal IGF2 expression could affect risk for GDM. Moreover, in an epidemiological study among 1160 mother/partner/offspring trios from the UK, Petry et al found that polymorphic variations in the paternally transmitted fetal IGF2 genotype, but not the maternal or maternally transmitted fetal IGF2 genotypes, were associated with increased maternal glucose concentrations in pregnancy, which could potentially alter the risk of maternal GDM (Petry et al, 2011). These studies highlighted a potential role of the paternal and fetal genomes, in addition to the maternal genome itself, in maternal glucose homeostasis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In women with certain maternal gene polymorphisms, fetal sex influenced important parameters of maternal physiology during pregnancy, including those of the glucose metabolism [23][24][25]. Moreover, paternally transmitted gene variants of the fetal IGF2 gene (which encodes insulin-like growth factor-II) were associated with increased maternal glucose concentrations, thus potentially altering her risk of developing gestational diabetes mellitus [28].…”
Section: Fetal Metabolites Associated With Maternal Gdmmentioning
confidence: 99%
“…Other potentially contributing factors discussed in the literature include chronic low-grade inflammation [20], different genetic, epigenetic and non-genetic environmental factors including nutrition [21][22][23][24][25][26]. Moreover, fetal sex [23,27] and fetal genes [28] have been shown to correlate with maternal glucose concentrations during pregnancy and thus may modulate the risk for maternal GDM. However, it is not clear if the fetus can impact on the maternal organism in such a regulating manner.…”
Section: Introductionmentioning
confidence: 99%